Research progress in refractory sudden hearing loss: steroid therapy. Issue 1 (January 2020) - Liu, Ya; Chen, Qiongqiong; Xu, Yaping
Sudden sensorineural hearing loss (SSNHL) is a common condition with a rapid onset, and its worldwide frequency is increasing each year. Importantly, a significant number of patients with SSNHL do not respond to initial treatment, which is termed refractory sudden hearing loss (RSHL), and further treatment is not standardized in terms of type, duration, administration route, and concentration of topical steroid therapy. Dexamethasone and methylprednisolone are effective in treating RSHL, and salvage treatment typically consists of 2 weeks of steroid therapy followed by 3–6 months of follow-up. Near-continual steroid perfusion appears to be more effective than intermittent steroid injection. Furthermore, several novel therapeutic regimens have shown promising results in small-scale studies. However, the optimum treatment needs to be confirmed in larger randomized controlled trials.